PENGARUH CITA RASA DAN VARIASI MENU TERHADAP TINGKAT KEPUASAAN KONSUMEN DI RUMAH MAKAN ANEKA SEBLAK SEI PANAS KOTA BATAM - Miratia Afriani; Tito Pratama (JURNAL MATA PARIWISATA, 2022)
This study aims to determine the effect of taste and menu variations on the level of consumer satisfaction at Aneka Seblak Sei Panas Restaurant, Batam City. The research used is quantitative research. The population used in this study are consumers who are at Aneka Seblak Restaurant. The sampling technique used is accidental sampling, which is based on chance, which means that consumers buy products at Aneka Seblak Restaurant. The number of samples in this study were 300 respondents who were consumers of Aneka Seblak Restaurant. The data collection method used in this research is by distributing questionnaires. The data analysis technique used in this research is the multiple linear regression method, T test, F test and the determinant coefficient (R2) with SPSS 26 program. The results of the normality test from the Kolmogorov Smirnov test showed that the residual research data had a normal distribution of 0.267 > 0.05. The results of the multicollinearity test and heteroscedasticity test showed that all variables were free from the symptoms of multicollinearity and heteroscedasticity. The results of the multiple linear test show that all independent variables are positive. That is, if there is an increase of 1%, the value of the dependent variable will also increase. The results of this study indicate that (1) the results of the T test on the taste variable (X1) are 2.133 > 1.96790301, Menu variation (X2) is 4.926 > 1.96790301,. So, it can be concluded that there are taste variables and menu variations partially on the level of consumer satisfaction. (2) There is a simultaneous influence of taste and menu variations on purchasing decisions as evidenced by Fcount > Ftable, 217,014 > 3.0261 and getting the percentage contribution (R2) of 59.4% and the remaining 40.6% is influenced by other variables